Recent developments in two-dimensional materials-based membranes for oil–water separation - Ezazi, Mohammadamin; Quazi, Moinuddin Mohammed (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The industrialization witnessed in the last century has resulted in an unprecedented increase in water pollution. In particular, the water pollution induced by oil contaminants from oil spill accidents, as well as discharges from pharmaceutical, oil/gas, and metal processing industries, have raised concerns due to their potential to pose irreversible threats to the ecosystems. Therefore, the effective treating of these large volumes of oily wastewater is an inevitable challenge to address. Separating oil–water mixtures by membranes has been an attractive technology due to the high oil removal efficiency and low energy consumption. However, conventional oil–water separation membranes may not meet the complex requirements for the sustainable treatment of wastewater due to their relatively shorter life cycle, lower chemical and thermal stability, and permeability/selectivity trade-off. Recent advancements in two-dimensional (2D) materials have provided opportunities to address these challenges. In this article, we provide a brief review of the most recent advancements in oil–water separation membranes modified with 2D materials, with a focus on MXenes, graphenes, metal–organic frameworks, and covalent organic frameworks. The review briefly covers the backgrounds, concepts, fabrication methods, and the most recent representative studies. Finally, the review concludes by describing the challenges and future research directions.